Non-hematologic predictors of mortality improve the prognostic value of the international prognostic scoring system for MDS in older adults. Issue 4 (July 2015) - Fega, K. Rebecca; Abel, Gregory A.; Motyckova, Gabriela; Sherman, Alexander E.; DeAngelo, Daniel J.; Steensma, David P.; Galinsky, Ilene; Wadleigh, Martha; Stone, Richard M.; Driver, Jane A.
Abstract Objectives The International Prognostic Scoring System (IPSS) is commonly used to predict survival and assign treatment for the myelodysplastic syndromes (MDS). We explored whether self-reported and readily available non-hematologic predictors of survival add independent prognostic information to the IPSS. Materials and Methods Retrospective cohort study of consecutive MDS patients ≥ age 65 who presented to Dana-Farber Cancer Institute between 2006 and 2011 and completed a baseline quality of life questionnaire. Questions corresponding to functional status and symptoms and extracted clinical-pathologic data from medical records. Kaplan–Meier and Cox proportional hazards models were used to estimate survival. Results One hundred fourteen patients consented and were available for analysis. Median age was 73 years, and the majority of patients were White, were male, and had a Charlson comorbidity score of < 2. Few patients (24%) had an IPSS score consistent with lower-risk disease and the majority received chemotherapy. In addition to IPSS score and history of prior chemotherapy or radiation, significant univariate predictors of survival included low serum albumin, Charlson score, performance status, ability to take a long walk, and interference of physical symptoms in family life. The multivariate model that best predicted mortality included low serum albumin (HR = 2.3; 95% CI: 1.06–5.14), therapy-related MDS (HR = 2.1; 95% CI: 1.16–4.24), IPSS score (HR = 1.7; 95% CI: 1.14–2.49), and ease taking a long walk (HR = 0.44; 95% CI: 0.23–0.90). Conclusions In this study of older adults with MDS, we found that low serum albumin and physical function added important prognostic information to the IPSS score. Self-reported physical function was more predictive than physician-assigned performance status.